Exploring Amantadine Derivatives as Urease Inhibitors: Molecular Docking and Structure–Activity Relationship (SAR) Studies - Atteeque Ahmed; Aamer Saeed; Omar M. Ali; Zeinhom M. El-Bahy; Pervaiz Ali Channar; Asma Khurshid; Arfa Tehzeeb; Zaman Ashraf; Hussain Raza; Anwar Ul-Hamid; Mubashir Hassan (Molecules, 2021)
This article describes the design and synthesis of a series of novel amantadine-thiourea conjugates (3a–j) as Jack bean urease inhibitors. The synthesized hybrids were assayed for their in vitro urease inhibition. Accordingly, N-(adamantan-1-ylcarbamothioyl)octanamide (3j) possessing a 7-carbon alkyl chain showed excellent activity with IC50 value 0.0085 ± 0.0011 µM indicating that the long alkyl chain plays a vital role in enzyme inhibition. Whilst N-(adamantan-1-ylcarbamothioyl)-2-chlorobenzamide (3g) possessing a 2-chlorophenyl substitution was the next most efficient compound belonging to the aryl series with IC50 value of 0.0087 ± 0.001 µM. The kinetic mechanism analyzed by Lineweaver–Burk plots revealed the non-competitive mode of inhibition for compound 3j. Moreover, in silico molecular docking against target protein (PDBID 4H9M) indicated that most of the synthesized compounds exhibit good binding affinity with protein. The compound 3j forms two hydrogen bonds with amino acid residue VAL391 having a binding distance of 1.858 Å and 2.240 Å. The interaction of 3j with amino acid residue located outside the catalytic site showed its non-competitive mode of inhibition. Based upon these results, it is anticipated that compound 3j may serve as a lead structure for the design of more potent urease inhibitors.